Epidemiology and Risk Factors for Orthostatic Hypotension and Its Severity in Residents Aged > 60 years: A Cross-Sectional Study - Mingni Yang; Ruiqiang Peng; Zetuo Wang; Miaoduan Li; Yehua Song; Jianping Niu; Yong Ji (International Journal of Hypertension)
This cross-sectional study investigated the epidemiology and risk factors associated with orthostatic hypotension (OH) and its severity in older adults residing in the Jizhou community of Tianjin and the Jimei community of Xiamen. The study, conducted from March to September 2019, involved adults aged over 60. A comprehensive questionnaire survey was administered, resulting in the enrolment of 4383 older adults. The overall prevalence of OH was found to be 11.7% (516 out of 4383). Notably, a significant gender difference was observed, with a prevalence of 10% among males (194 out of 1926) and 13.1% among females (322 out of 2457) (P=0.002). Among individuals with OH, 332 exhibited mild symptoms, 64 had moderate OH, 58 had severe OH cases, and 50 have very severe OH. Multivariable logistic regression analysis revealed that being female, widowed, engaging in general social activities, and a history of hypertension, migraines, heart disease, cerebrovascular disease, and mental health conditions (anxiety and depression) were independently associated with OH. Ordinal logistic regression analysis further confirmed that hypertension, migraine, and a history of general anesthesia surgery were independently associated with the severity of OH. This study highlights a relatively high prevalence of OH among older adults in the Jizhou community of Tianjin and the Jimei community of Xiamen, China. The identified risk factors, particularly social activities, and hypertension, significantly influence the severity of OH. Further examination is required to corroborate these findings and investigate potential interventions.